2016
DOI: 10.1007/s00360-016-1011-3
|View full text |Cite
|
Sign up to set email alerts
|

Natural variations of cold tolerance and temperature acclimation in Caenorhabditis elegans

Abstract: Temperature is critical for the survival and proliferation of animals, which must be adapted to cope with environmental temperature changes. In this study, we demonstrated natural variations in the phenotypes of temperature tolerance and temperature acclimation of the nematode Caenorhabditis elegans, and we decoded whole genome sequence of six natural variations, which enabled us to map responsible gene polymorphisms onto specific chromosomal regions. The C. elegans laboratory strain, N2, survives at 2 °C afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 18 publications
(31 reference statements)
0
34
0
1
Order By: Relevance
“…In addition to Songpu mirror carp and Barbless carp, organisms including zebra sh [33,34], Caenorhabditis elegans [44,45] and plants [46] possess a cold acclimation ability to allow their survival in extremely low temperature. In this study, many genes that are previously reported to associate with the cold acclimation of zebra sh [33] were found to be differentially expressed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Songpu mirror carp and Barbless carp, organisms including zebra sh [33,34], Caenorhabditis elegans [44,45] and plants [46] possess a cold acclimation ability to allow their survival in extremely low temperature. In this study, many genes that are previously reported to associate with the cold acclimation of zebra sh [33] were found to be differentially expressed.…”
Section: Discussionmentioning
confidence: 99%
“…C. elegans exhibits cold tolerance and temperature acclimatisation, which are useful model for studying temperature sensation at the molecular and cellular levels 6 , 9 . Wild-type animals demonstrate a form of acclimatisation related to cold tolerance, which was defined as temperature acclimatisation 5 , 10 . For example, 15 °C-cultivated animals survive at 2 °C, whereas 25 °C-cultivated animals can not survive at 2 °C (Fig.…”
mentioning
confidence: 99%
“…However, these mechanisms are complex and remain elusive. Exploiting well-established genetic approaches (1,2), the nematode Caenorhabditis elegans has been used as a simple model useful in the study of temperature behaviors and tolerance (3)(4)(5). C. elegans is known to exhibit cold tolerance in response to environmental temperature decrease (4,6), and previous research described cold tolerance as regulated through ASJ sensory neuron, intestine, and sperm tissue networks (4,6).…”
mentioning
confidence: 99%